Escola Técnica do Comércio em Cuiabá (1945-1957) - Corrêa, Giselle Estevam Chiozini (2020)
This research has as study object the school’s culture of the Technical Trade School of Cuiabá. This institution offered the technical trade education and it was created by the year of 1945. The study is part of the Research line Culture, Memories and Education Theories inside the Post-graduation Program in the Education of UFMT. The theoretical base is the Cultural History and also the history of the Education Institution based on Justine Magalhães. It was also used as theoretical base the contributions of Roger Chartier, José Luís Sanfelice, Domimique Julia and Ivor F. Goodson among others. The methodology used was the qualitative analysis of historical approach, and it was used as research sources the Official Legislation, Reports made by the Intendant and by the Mato Grosso’s governor, all available in the Public Archive of Mato Grosso (APMT), in the Center of Education’s Documentation of Mato Grosso, in the Core of the Historical Information and Documentation of Schools in Mato Grosso – NDIHR, and also in the National Library. It was also done a bibliographic review using the data of papers, dissertations and other available materials in this database. The investigation period is delimited because 1945 was the year that the School was created until the date that the documentation about the functioning of the school was founded. The dissertation on discussing the education cultural aspects prioritizing the syllabus analysis, it observes the relationships inside the school’s wall and how the national standards influenced the local standards. Discussing about the directions that legislation took, it is possible to perceive by the documentation sources analysis that it divided the contents in Contents of Technical Culture and Contents of General Culture and both of them were characterized by the professionalization approach. The documents also indicates that the state public agents perceived the importance of the Trade Education that was happening in the Nation and they led the administration authorities to invest in the creation and expansion of this education modality. Their first act was the creation of the Technical Trade School in Cuiabá.